Use of an artificial crown pillar in transition from open pit to underground mining. (May 2019) - Xu, Shuai; Suorineni, Fidelis T.; An, Long; Li, Yuan Hui; Jin, Chang Yu
Abstract: In the transition from open pit to underground mining, a crown pillar is usually left at the open pit bottom. Crown pillars are often not recovered and as a result they are deemed as permanent losses. To address this problem, this paper discusses use of an artificial crown pillar as replacement for the natural crown pillar during a transition from open-pit to underground mining. The substitution of the natural crown pillar with an artificial one enabled total recovery of sterilized ore in the natural crown pillar. A case study is presented on Shandong Guilai Village Gold Mine open pit transition to underground mining. The safe and profitable mining of the natural crown pillar, and the simultaneous construction of the artificial crown pillar was achieved by combined use of analytical and empirical methods, numerical modelling and instrumentation. The analytical and empirical methodologies were used to determine the natural crown pillar thickness. Numerical modelling was performed to further evaluate the results of the analytical and empirical methods, and to predict the performances of the artificial crown pillar. The instrumentation monitoring ensured safety of the open pit slopes and underground infrastructure prior to, during and after the process of mining and simultaneous construction of the artificial crown pillar. It was concluded that the process of simultaneously mining the natural crown pillar and replacing it with an artificial one was successful in protecting the open pit slopes and underground infrastructure. A comparison of the cost of mining the natural crown pillar, processing the ore and constructing the artificial crown pillar with the market price of the gold obtained showed a profit of 30%. While this study is limited to a particular mine, the procedure could be used in other mines in similar situations. Highlights: An artificial crown pillar is used to replace a natural ore rock crown pillar. The stability of the artificial and natural rock crown pillars is analyzed. Empirical, analytical, and numerical modelling are used in the stability analysis. Monitoring during the mining and construction process ensured safety. Use of the artificial crown pillar enabled safe recovery of ore rock at profit.